Article 10: Promotion, protection and treatment of investments - Mejía-Lemos, Diego (Edward Elgar Publishing, 2023)
This chapter provides a commentary of Article 10 of the Energy Charter Treaty (ECT). The commentary places emphasis on the ways in which Article 10 has been interpreted and applied by various arbitral tribunals constituted pursuant to the ECT. This chapter is based on a comprehensive survey of decisions of those ECT arbitral tribunals and the existing literature on Part III and Article 10. Article 10 belongs to Part III. Part III sets out obligations regarding 'promotion, protection and treatment' of investments under the ECT. Article 10 is a complex provision, which comprises Article 10(1) and 10(2)-10(12), and sets out the standards of investment protection under the ECT. Article 10(1), in particular, is divided into 'five sentences'. The ECT and Article 10, in particular, do not operate in a vacuum, but as a special system of treaty law within the broader framework of general international law. Consequently, this chapter addresses various general international law questions arising in connection with arbitrations under the ECT, including issues governed by the law of treaties and the law of international responsibility.